Modelling the composition of government expenditure - Creedy, John 1949- (Edward Elgar, 2011)
"The composition of government expenditure varies considerably across countries. The aim of this book is to explore the choice of expenditure using a range of modelling approaches. The models allow for different economic environments, involving the types of expenditure considered, the time period of analysis and the behaviour of individuals. The composition of expenditure is examined using majority voting and public finance frameworks, where the latter involves maximisation of a social welfare function involving a trade-off between equity and efficiency. Special attention is given to expenditure on transfer payments, public goods and education. Empirical analyses are also carried out, using data for a wide range of countries, where potential orders of magnitude of various components of the models are obtained. The models help in considering important factors and the inter-relationships involved. In particular, a synthesis is provided which allows special consideration of the role of basic inequality in influencing expenditure patterns. The book will be of considerable value to students and researchers interested in public economics."--Back cover.